2020
DOI: 10.1021/acssuschemeng.9b06432
|View full text |Cite
|
Sign up to set email alerts
|

Combining Selective Extraction and Easy Stripping of Lithium Using a Ternary Synergistic Solvent Extraction System through Regulation of Fe3+ Coordination

Abstract: Lithium is becoming increasingly important due to its essential role in lithium-ion batteries. Over 70% of the global lithium resources are found in salt lake brines, where lithium is always accompanied by magnesium. The system of TBP (tributyl phosphate)/FeCl3 has been widely studied for selective lithium extraction from high Mg-containing salt lake brines. However, the system requires a high concentration of HCl for lithium stripping, which causes equipment corrosion, consumes large amounts of reagents and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…The TBP/FeCl 3 system has been intensively studied for the selective extraction of Li from high Mg‐Li ratio brines by other researchers, 14‐20 but the C923/FeCl 3 system has not been reported yet. The two systems are compared here for their extraction performance from a synthetic brine solution containing 0.10 mol·L −1 LiCl and 4.0 mol·L −1 MgCl 2 (Figure 2), which is a typical composition of concentrated brine 11,16,19 . The extraction of Li by the TBP/FeCl 3 system increased from 62% at 0.10 mol·L −1 FeCl 3 to 81% at 0.20 mol·L −1 FeCl 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TBP/FeCl 3 system has been intensively studied for the selective extraction of Li from high Mg‐Li ratio brines by other researchers, 14‐20 but the C923/FeCl 3 system has not been reported yet. The two systems are compared here for their extraction performance from a synthetic brine solution containing 0.10 mol·L −1 LiCl and 4.0 mol·L −1 MgCl 2 (Figure 2), which is a typical composition of concentrated brine 11,16,19 . The extraction of Li by the TBP/FeCl 3 system increased from 62% at 0.10 mol·L −1 FeCl 3 to 81% at 0.20 mol·L −1 FeCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…13 Because of the low cost of TBP and FeCl 3 and the good Li/Mg selectivity of this solvent extraction system, it has been studied extensively. [14][15][16][17][18][19][20] In the synergic solvent extraction of Li by the TBP/FeCl 3 Cyanex 923 (C923, a commercial mixture of trialkyl phosphine oxides with mainly n-hexyl and n-octyl, shown in Figure 1) is a popular commercial neutral extractant that is similar to TBP. It has been used in the extraction of a wide range of metals, including rare earth elements (REEs), transition metals, and precious metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El-Eswed et al [205] investigated the organophosphorus ligands phenylphosphonic, phenylphosphinic and bis(2-ethylhexyl) phosphoric acid and observed that by adding ammonia to the aqueous phase, lithium extraction increased as high as 90% with bis(2-ethylhexyl) phosphoric acid. Neutral extraction systems containing TBP, FeCl 3 , and kerosene have been extensively investigated for lithium extraction [63,179,183,206,207]. In this solvent extraction approach, kerosene is the diluent, TBP serves as a neutral organophosphorus extractant, and FeCl 3 is the co-extraction reagent [63,179,183].…”
Section: Extractants Cas Number Formula Structural Formulamentioning
confidence: 99%
“…It seems that the Mg/Li selectivity of single‐extractant SX systems (Such as D2EHPA and Versatic Acid 10) is limited. Synergic SX systems (using mixtures of two or more extractants) often have much‐improved separation performance compared with single‐extractant systems 21‐24 . β‐diketones and some neutral ligands have been found to have synergism for Li extraction since the 1960s.…”
Section: Introductionmentioning
confidence: 99%